(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the physical-chemical characteristics and sugar profile of the sapodilla pulp. The sapodilla pulp in natura was characterized in triplicate regarding the following physical-chemical parameters: water content, water activity, pH, total titratable acidity, total soluble solids, ratio, ash, ascorbic acid content, total sugars, reducers and non-reducing sugars. The determination of the sugar profile was performed using a high performance liquid chromatography system (HPLC) and the sugar concentration was determined from standard curves. The water content obtained was 76.21% and water activity 0.991. The ratio parameter showed a value of 81.82, indicating an elevated degree of sweetness. The levels of total, reducing and non-reducing sugars were 12.38% glucose, 10.81% glucose and 1.57% sucrose respectively. The sugar profile of the pulp showed that glucose had the highest content (5.98 g/100g) followed by fructose (4.85 g/100g) and maltose (0.017 g/100g). Thus, the sapodilla pulp can be used as raw material in sweet food formulations due to the sugar profile, which contributes to the industrial valorization of the fruit.